2020
DOI: 10.7554/elife.57011
|View full text |Cite
|
Sign up to set email alerts
|

Sleep spindles mediate hippocampal-neocortical coupling during long-duration ripples

Abstract: Sleep is pivotal for memory consolidation. According to two-stage accounts, memory traces are gradually translocated from hippocampus to neocortex during non-rapid-eye-movement (NREM) sleep. Mechanistically, this information transfer is thought to rely on interactions between thalamocortical spindles and hippocampal ripples. To test this hypothesis, we analyzed intracranial and scalp Electroencephalography sleep recordings from pre-surgical epilepsy patients. We first observed a concurrent spindle power increa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
134
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(162 citation statements)
references
References 73 publications
13
134
0
Order By: Relevance
“…That said, a recent iEEG study has shown that both hippocampal ripples and hippocampal-cortical interactions are most eminent when preceded by a cortical SOspindle complex 20 . To the extent that reactivation observed here is linked to hippocampal engagement, the timing of our effects (Fig.2 a-b) is consistent with accumulating evidence that the hippocampal-cortical dialogue is in fact initiated by cortex 20,21,[57][58][59] . One tentative interpretation of our results might thus be that cortical SO-spindle complexes trigger hippocampal memory reactivation while ensuring that the cortical target area is optimally tuned for synaptic plasticity 15,17,60 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…That said, a recent iEEG study has shown that both hippocampal ripples and hippocampal-cortical interactions are most eminent when preceded by a cortical SOspindle complex 20 . To the extent that reactivation observed here is linked to hippocampal engagement, the timing of our effects (Fig.2 a-b) is consistent with accumulating evidence that the hippocampal-cortical dialogue is in fact initiated by cortex 20,21,[57][58][59] . One tentative interpretation of our results might thus be that cortical SO-spindle complexes trigger hippocampal memory reactivation while ensuring that the cortical target area is optimally tuned for synaptic plasticity 15,17,60 .…”
Section: Discussionsupporting
confidence: 89%
“…Lastly, hippocampal ripples are transient network oscillations and have been closely linked to reactivation/replay of learning experiences 18,19 . They have been shown to occur in the excitable troughs of the spindle, suggesting that spindles might facilitate information transfer from the hippocampus to neocortical target sites 20,21 . The efficacy of systems consolidation through memory reactivation might thus hinge on concurrent SO-spindle coupling, ensuring optimal conditions to ignite structural changes in cortical target sites 7,10,22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Sleep data was recorded overnight, during which polysomnography (PSG) recordings were performed to allow sleep staging. Following prior methods (Iber and American Academy of Sleep Medicine., 2007;Staresina et al, 2015;Ngo et al, 2020), PSG data was classified into awake, rapid-eye movement (REM) and non-REM (NREM) sleep states. We recorded 736 minutes (12.27 hours) of PSG data where 203 minutes (27.6%)…”
Section: Sleep Recordingmentioning
confidence: 99%
“…After pre-processing steps, ripple events were identified in three general stages: i) time domain detection for identifying putative ripple events; ii) frequency domain assessment for accepting/rejecting ripple events; iii) electrode wise ripple count thresholding for inclusion/exclusion. Analytic criteria were based on prior human hippocampal ripples studies (Staresina et al, 2015;Helfrich et al, 2019;Jiang et al, 2019;Jiang et al, 2020;Ngo et al, 2020), as detailed below.…”
Section: Data Analysis: Ripple Detection and Rejectionmentioning
confidence: 99%
See 1 more Smart Citation